The Relationship Between Cumulative Platinum-Based Chemotherapy Dose And The Occurrence Of Ototoxicity In Head And Neck Malignancies - Hendro Purnomo; Dwi Marliyawati; Muyassaroh Muyassaroh; Dian Ayu Ruspita; Zulfikar Naftali (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND: Chemotherapy is a treatment for head and neck malignancies. Hearing impairment is a side effect of chemotherapy, especially caused by platinum-based chemotherapy. Hearing impairment generally occurs at high frequencies after the administration of chemotherapy. AIMS: To prove assosciation between cumulative doses of platinum-based chemotherapy and ototoxic events in head and neck malignancies. METHOD: This is a cross-sectional study. The sample is patients with head and neck malignancy receiving platinum-based chemotherapy at Dr. Kariadi Hospital Semarang from March to June 2023. Hearing assessment using pure tone audiometry was performed randomly at all chemotherapy cycles. Data was analyzed with a chi-square test. RESULT:  Eighty-one subjects (52 male, 29 female), consisting of 71 subjects received cisplatin, and 10 subjects received carboplatin. Ototoxicity occurs in 91.7% of subjects receiving cumulative doses of cisplatin >300mg/m2 and carboplatin >1500mg/m2 compared to cumulative doses of cisplatin <300mg/m2 and carboplatin <1500mg/m2, which was 46.7% (p = 0.001, CI 1.416-2.725). CONCLUSION: There was a significant association between cumulative doses of platinum-based chemotherapy and ototoxicity incidence of head and neck malignancy patients.